Unbiased Phenotype-Based Screen Identifies Therapeutic Agents Selective for Metastatic Prostate Cancer - Chung, Ivy; Zhou, Kun; Barrows, Courtney; Banyard, Jacqueline; Wilson, Arianne; Rummel, Nathan; Mizokami, Atsushi; Basu, Sudipta; Sengupta, Poulomi; Shaikh, Badaruddin; Sengupta, Shiladitya; Bielenberg, Diane R.; et al. (Frontiers in Oncology, 2021)
In American men, prostate cancer is the second leading cause of cancer-related death. Dissemination of prostate cancer cells to distant organs significantly worsens patients’ prognosis, and currently there are no effective treatment options that can cure advanced-stage prostate cancer. In an effort to identify compounds selective for metastatic prostate cancer cells over benign prostate cancer cells or normal prostate epithelial cells, we applied a phenotype-based in vitro drug screening method utilizing multiple prostate cancer cell lines to test 1,120 different compounds from a commercial drug library. Top drug candidates were then examined in multiple mouse xenograft models including subcutaneous tumor growth, experimental lung metastasis, and experimental bone metastasis assays. A subset of compounds including fenbendazole, fluspirilene, clofazimine, niclosamide, and suloctidil showed preferential cytotoxicity and apoptosis towards metastatic prostate cancer cells in vitro and in vivo. The bioavailability of the most discerning agents, especially fenbendazole and albendazole, was improved by formulating as micelles or nanoparticles. The enhanced forms of fenbendazole and albendazole significantly prolonged survival in mice bearing metastases, and albendazole-treated mice displayed significantly longer median survival times than paclitaxel-treated mice. Importantly, these drugs effectively targeted taxane-resistant tumors and bone metastases – two common clinical conditions in patients with aggressive prostate cancer. In summary, we find that metastatic prostate tumor cells differ from benign prostate tumor cells in their sensitivity to certain drug classes. Taken together, our results strongly suggest that albendazole, an anthelmintic medication, may represent a potential adjuvant or neoadjuvant to standard therapy in the treatment of disseminated prostate cancer.